To what extent is socioeconomic status associated with not taking up and dropout from cardiac rehabilitation: a population-based follow-up study - Thomas Maribo; Christina M Stapelfeldt; Marie Louise Svendsen; Birgitte Bitsch Gadager; Maiken Bay Ravn; Sanne Moeller Palner (BMJ Open)
Objectives High socioeconomic status (SES) has been linked to high referral for cardiac rehabilitation (CR). However, the impact of SES on CR utilisation from enrolment to completion is unclear. The objective of this study was to examine whether indicators of SES are associated with not taking up and dropout from CR.Design A population-based, follow-up study.Setting Hospitals and primary healthcare centres in the Central Denmark Region.Participant Patients diagnosed with ischaemic heart disease (IHD) in the hospital and referred for rehabilitation in the primary healthcare setting from 1 September 2017 to 31 August 2018 (n=2018).Variables Four SES indicators (education, disposable family income, occupation and cohabitant status) were selected because of their established association with cardiovascular health and CR utilisation. Patients were followed up regarding no uptake of or dropout from CR in the primary healthcare setting.Statistical methods The associations between the four SES indicators and either no uptake or dropout from CR were analysed using logistic regression with adjustment for age, sex, nationality and comorbidity.Results Overall, 25% (n=507) of the referred patients did not take up CR and 24% (n=377) of the participators dropped out the CR. All adjusted ORs, except one (education/dropout) demonstrated that low SES compared with high are statistically significantly associated with higher odds of not taking up CR and dropout from CR. The ORs ranged from 1.52, 95% CI 1.13 to 2.04 (education/no uptake) to 2.36, 95% CI 1.60 to 3.46 (occupation/dropout).Conclusions This study highlights that indicators of SES are important markers of CR utilisation following hospitalisation for IHD.